Fuel poverty in Ireland : Extent, affected groups and policy issues - Sue Scott; Seán Lyons; Claire Keane; Donal McCarthy; Richard S. J. Tol (The Economic and Social Research Institute (ESRI), 2008)
This paper provides updated estimates for the scale of fuel poverty in the Republic of Ireland using two measures: one based on fuel expenditure as a share of income and the other based on self-reported deprivation. It also presents modelling results as to the characteristics of households most vulnerable to fuel poverty, examines the potential effects of future fuel price changes, outlines policies in place in Ireland and other countries, and discusses policy issues.
Keywords: 330; Brennstoff; Angebot; Preisniveau; Verbraucherausgaben; Armut; Prognose; Irland